The clinical decision-making of Vietnamese nursing students and related factors: A cross-sectional survey - Yen Quach, Tran Binh; Lan Nguyen, Thi Phuong; Hong Huynh, Thuy Phuong (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Clinical decision-making is a critical competency in nursing, influencing patient safety and career satisfaction. However, the factors shaping clinical decision-making remain underexplored, particularly in Vietnam, where research on this topic is limited. Understanding these factors is essential for enhancing nursing education and clinical practice. Objective: To assess clinical decision-making skills among nursing students, examining their relationship with students’ characteristics, perceptions of the clinical environment, and grade point average (GPA). Methods: This cross-sectional study surveyed 189 nursing students in the University of Medicine and Pharmacy at Ho Chi Minh City using an online questionnaire in June 2021. Clinical decision-making styles were assessed using the Nurses Decision-Making Instrument Revised - 2014 (NDMI-R14), and the clinical learning environment (CLE) was evaluated with the Vietnamese-CLEI. To assess differences between variables, Chi-square tests were applied, or Fisher’s exact tests where appropriate. Correlation between variables was examined using Pearson’s correlation coefficient for parametric data or Spearman’s rank correlation for non-parametric data. Results: The average clinical decision-making score was 68.6, with 67.7% of students demonstrating a quasi-rational decision-making style and 32.3% relying solely on analysis. Notably, no students reported exclusively intuitive decision-making. Significant negative correlations were identified between clinical decision-making scores and extracurricular activities (r = -0.20, p = 0.005), clinical learning environment (rs (187) = -0.16, p = 0.027), and GPA (r = -0.18, p = 0.011). These findings suggest that students with higher academic performance and greater extracurricular involvement were less likely to rely on intuitive decision-making. Conclusion: Vietnamese nursing students predominantly exhibited a quasi-rational decision-making style, combining intuition and analysis. However, students with higher GPA and extracurricular engagement showed reduced intuitive reasoning, highlighting a potential gap in their decision-making development. Nursing education programs in Vietnam should focus on fostering analytical and intuitive reasoning skills to prepare students for complex clinical environments. Further research is needed to explore the cultural, educational, and contextual factors influencing these patterns.